Terapi Penggantian Testosterone pada Hipogonadisme Onset Lambat: Tinjauan Pustaka - Mahendro, Della (PT Kalbe Farma Tbk., 2026)
Testosterone is a sex hormone that plays a critical role in various physiological functions in men, including regulating libido, muscle mass, fat composition, and bone health. Late-onset hypogonadism, which commonly occurs in older men, reflects age-related declines in testosterone levels and can be associated with chronic disease and adiposity. Diagnosis requires a comprehensive evaluation, including clinical symptoms and repeated morning serum testosterone levels. Testosterone replacement therapy (TRT) is a common treatment approach for symptomatichypogonadism, with dosage options including oral, intramuscular, transdermal, subdermal, and nasal. However, TRT has contraindications, particularly in men with active prostate cancer, high hematocrit, or certain cardiovascular diseases. Appropriate monitoring of therapy is necessary to evaluate the effectiveness of therapy, optimize dosage, and detect side effects such as polycythemia or elevated PSA. The primary goal of TRT in men with testosterone deficiency is to restore testosterone levels to the physiological range to improve sexual function, muscle strength, and quality of life in men with hypogonadism.